2022
DOI: 10.1039/d2re00003b
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of activated carbon from low-rank coal via alkali activation and its fundamental CO2 adsorption capacity at ambient temperature under pure pressurized CO2

Abstract: The relationship between the CO2 adsorbed amount and specific surface area (a) or pore volumes (b) of the prepared activated carbon. The open plot is the prepared activated carbon. The solid plot is the activated carbon prepared from BN, TN, and SO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…The activation mechanism of K 2 CO 3 is shown in eqs and . In addition, K 2 CO 3 has a strong catalytic effect on coal gasification, in which it can catalyze coal to release more gas, thus promoting the formation of pore structure. Mochizuki et al studied the influence of different mixing ratios of lignite, melamine, and K 2 CO 3 , activation temperatures and activation times on the CO 2 adsorption performance, and pore structure of CAC prepared using lignite as the raw material. The results showed that CAC obtained at a ratio of lignite, melamine, and K 2 CO 3 of 1:1:2, an activation temperature of 900 °C, and an activation time of 1 h had the highest BET specific surface area, total pore volume, and micropore volume.…”
Section: Preparation Of Cacmentioning
confidence: 99%
“…The activation mechanism of K 2 CO 3 is shown in eqs and . In addition, K 2 CO 3 has a strong catalytic effect on coal gasification, in which it can catalyze coal to release more gas, thus promoting the formation of pore structure. Mochizuki et al studied the influence of different mixing ratios of lignite, melamine, and K 2 CO 3 , activation temperatures and activation times on the CO 2 adsorption performance, and pore structure of CAC prepared using lignite as the raw material. The results showed that CAC obtained at a ratio of lignite, melamine, and K 2 CO 3 of 1:1:2, an activation temperature of 900 °C, and an activation time of 1 h had the highest BET specific surface area, total pore volume, and micropore volume.…”
Section: Preparation Of Cacmentioning
confidence: 99%